Does vitamin A supplementation protect schoolchildren from acquiring soil-transmitted helminthiasis? A randomized controlled trial - Al-Mekhlafi, H.M.; Anuar, T.S.; Al-Zabedi, E.M.; Al-Maktari, M.T.; Mahdy, M.A.K.; Ahmed, A.; Sallam, A.A.; Abdullah, W.A.; Moktar, N.; Surin, Johari (BMC, 2014)
Background